Profile Of Antihypertensive Drug Use At Clinic M Surabaya : Profil Penggunaan Obat Antihipertensi di Klinik M Surabaya - Diana Rahmawati; Ninik Mas Ulfa (Akademi Farmasi Surabaya, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest/quiet. The purpose of this study was to determine the profile of the use of antihypertensive drugs at Clinic M Surabaya for the period July-December 2021. This study was conducted by collecting data retrospectively from July-December 2021 by screening and classifying antihypertensive drug prescriptions based on age and gender, drug class , generic name of the drug, dosage of the drug, rules for taking the drug. The number of samples that met the inclusion criteria were 552 recipes. From the study results, it was known that the patients with the most age were in the 56-65 year age group by 29.9%. Female patients were 51.1% more than male patients, namely 48.9%. The group of drugs that are often prescribed is the Calcium Channel Blocker group of 73.2%. The generic name of the drug that is often prescribed is Amlodipine as much as 72.9%, with a dose of 5 mg (59.1%) and the rule of use is 1 time a day after meals (27.2%).